Using Augmented Reality to Reduce Fear and Promote Cooperation During Pediatric Otolaryngologic Procedures. (4th September 2020) - Caruso, Thomas J.; Madill, Martine; Sidell, Douglas; Meister, Kara; Wang, Ellen; Menendez, Maria; Kist, Madison N.; Rodriguez, Samuel
Abstract : This case series examines interactive AR during minor otolaryngologic procedures. Although VR has been successfully used for pediatric vascular access, removing children from comforting people in the real world has resulted in patient anxiety. AR offers a potential advantage, utilizing distracting holographic images when patients maintain eye contact with parents. The primary objective was to determine the effect of AR on fear during pediatric otolaryngologic procedures. Secondary objectives included evaluating pain; procedure compliance; and patient, parent and physician attitudes toward AR, as well as assessing the feasibility of adding AR to a busy outpatient otolaryngologic clinic. Laryngoscope, 131:E1342–E1344, 2021